2016
DOI: 10.1159/000443120
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Hepatocyte-Like Cells with Functional Drug Transporters Directly-Reprogrammed from Mouse Fibroblasts and their Potential in Drug Disposition and Toxicology

Abstract: Background/Aims: To develop a suitable hepatocyte-like cell model that could be a substitute for primary hepatocytes with essential transporter expression and functions. Induced hepatocyte-like (iHep) cells directly reprogrammed from mice fibroblast cells were fully characterized. Methods: Naïve iHep cells were transfected with nuclear hepatocyte factor 4 alpha (Hnf4α) and treated with selected small molecules. Sandwich cultured configuration was applied. The mRNA and protein expression of transporters were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…AKT-mediated signaling accounts for fundamental cell functions such as cell proliferation, DNA repair, and antiapoptotic processes [34]. It has been reported that AKT activation occurs in solid tumors frequently [35]. A point mutation in AKT leads to its activation in a PI3K-independent manner [36].…”
Section: Discussionmentioning
confidence: 99%
“…AKT-mediated signaling accounts for fundamental cell functions such as cell proliferation, DNA repair, and antiapoptotic processes [34]. It has been reported that AKT activation occurs in solid tumors frequently [35]. A point mutation in AKT leads to its activation in a PI3K-independent manner [36].…”
Section: Discussionmentioning
confidence: 99%
“…5B). Three selected cholestatic drugs (rifampin, glibenclamide and ketoconazole) were reported as the inhibitors of BSEP (Ni et al, 2016;Wu et al, 2016). In this study, all of them significantly inhibited d8-TCA biliary excretion in SC-ProliHH-P (Fig.…”
mentioning
confidence: 56%
“…A was the concentration or amount of test compound accumulated in the absence (A minus_Ca++ ) or presence (A plus_Ca++ ) of Ca 2+ , which was achieved through adding warm Ca 2+ -free or standard HBSS buffer (Wu et al, 2016).…”
Section: Cyp Metabolic Capacity Determinationmentioning
confidence: 99%